An evaluation online registration for webOpac of Perpustakaan Sultanah Bahiyah - Mustapa, Azrain Nasyrah; Fadzilah, Budiman Ikhwandee (2012)
The university library exists to support the function of the university in terms of teaching and research which is particularly through its provision of adequate and relevant information resources that are supportive for faculty program needs.It is clear that the provision of up-to-date hard cover material and publications is limiting to which access to and downloading of information from computerized systems remains as a crucial factor.This makes the university library role is crucial in ensuring that the information materials are readily accessible with ease of sharing.Hence, the aim of the research was to determine the present level of acceptance for online registration and furthermore to identify factors that can affect the online registration users in using the system.The research model was developed from two dimensions named Theory of Reasoned Action (TRA) which was developed by Fishbein and Azjen and Technology Acceptance-Model (TAM), developed by Davis.The research was conducted at Universiti Utara Malaysia (UUM), Kedah.The respondents comprised of a sample of 100 Perpustakaan Sultanah Bahiyah employees. The questionnaire consisted of two sections, named demographic factor and the level of acceptance for online registration.Data were analyzed through independent t-test, one-way ANOVA and correlation. The statement "Assuming I have access to the online registration, I intend to use it" shows that 36.4 percent of the respondents disagree with this statement.In contrast, attitude towards online registration significantly associated with education level.The study also yielded evidence suggesting job position factor were significantly associated with attitude towards online registration. For example, the F value 10.367 is significant at the level 0.000.Thus, these revelations posed a challenge for Perpustakaan Sultanah Bahiyah to improve library staff competencies and skills such as information resources, information access, technology, management and research. Finally, some suggestions and direction for future researches have been forwarded to facilitate the online registration users.